2015
DOI: 10.1186/s12885-015-1976-4
|View full text |Cite
|
Sign up to set email alerts
|

Epirubicin: a new entry in the list of fetal cardiotoxic drugs? Intrauterine death of one fetus in a twin pregnancy. Case report and review of literature

Abstract: BackgroundCurrent knowledge indicate that epirubicin administration in late pregnancy is almost devoid of any fetal cardiotoxicity. We report a twin pregnancy complicated by breast cancer in which epirubicin administration was causatively linked to the death of one twin who was small for gestational age (SGA) and in a condition of oligohydramnios and determined the onset of a transient cardiotoxicity of the surviving fetus/newborn.Case presentationA 38-year-old caucasic woman with a dichorionic twin pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
1
7
0
3
Order By: Relevance
“…Because glucocorticoids regulate in a complex manner the P-gp transport system at gene transcription and translation levels they could have contributed to the risk for damage from anthracycline exposure [ 73 ]. We also confirmed epirubicin cardiotoxicity by finding high troponin levels and transient left ventricular septal hypokinesia in the surviving newborn [ 72 ].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Because glucocorticoids regulate in a complex manner the P-gp transport system at gene transcription and translation levels they could have contributed to the risk for damage from anthracycline exposure [ 73 ]. We also confirmed epirubicin cardiotoxicity by finding high troponin levels and transient left ventricular septal hypokinesia in the surviving newborn [ 72 ].…”
Section: Discussionsupporting
confidence: 61%
“…Conversely, although EPI has been considered devoid of cardiotoxic effects [ 66 70 ] one report describes transient ventricular hypokinesia [ 71 ]. In another report from our gynecological institute supported by myocardial and placental evidence we showed that epirubicin cardiotoxicity had a causative role in the death of a twin who died shortly after receiving glucocorticoids for lung maturation [ 72 ]. Because glucocorticoids regulate in a complex manner the P-gp transport system at gene transcription and translation levels they could have contributed to the risk for damage from anthracycline exposure [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Adverse cardiac foetal outcomes have been described after exposure to anthracyclines in utero, despite low transplacental passage. 14,18,54 Because of the different properties of the foetal myocardium as compared to the adult myocardium (single nucleus, fewer sarcomeres per mass unit, immature sarcoplasmic reticulum, lower number of mitochondria, underdeveloped antioxidant pathways), the foetal heart may be more vulnerable to anthracyclines. 55,56 Aviles et al reported the first study on the cardiac outcome after prenatal exposure to anthracyclines with normal echocardiographic findings for all children.…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…Due to their relatively low molecular weight, chemotherapeutic agents can cross the placenta and adversely affect the fetus [2][3][4]. Teratologic and other adverse fetal effects are dependent on dosage and the gestational age [5].…”
Section: Introductionmentioning
confidence: 99%